Using sparse polynomial chaos expansions for the global sensitivity analysis of groundwater lifetime expectancy in a multi-layered hydrogeological model. (March 2016) - Deman, G.; Konakli, K.; Sudret, B.; Kerrou, J.; Perrochet, P.; Benabderrahmane, H.
Abstract: The study makes use of polynomial chaos expansions to compute Sobol׳ indices within the frame of a global sensitivity analysis of hydro-dispersive parameters in a simplified vertical cross-section of a segment of the subsurface of the Paris Basin. Applying conservative ranges, the uncertainty in 78 input variables is propagated upon the mean lifetime expectancy of water molecules departing from a specific location within a highly confining layer situated in the middle of the model domain. Lifetime expectancy is a hydrogeological performance measure pertinent to safety analysis with respect to subsurface contaminants, such as radionuclides. The sensitivity analysis indicates that the variability in the mean lifetime expectancy can be sufficiently explained by the uncertainty in the petrofacies, i.e. the sets of porosity and hydraulic conductivity, of only a few layers of the model. The obtained results provide guidance regarding the uncertainty modeling in future investigations employing detailed numerical models of the subsurface of the Paris Basin. Moreover, the study demonstrates the high efficiency of sparse polynomial chaos expansions in computing Sobol׳ indices for high-dimensional models. Abstract : Highlights: Global sensitivity analysis of a 2D 15-layer groundwater flow model is conducted. A high-dimensional random input comprising 78 parameters is considered. The variability in the mean lifetime expectancy for the central layer is examined. Sparse polynomial chaos expansions are used to compute Sobol׳ sensitivity indices. The petrofacies of a few layers can sufficiently explain the response variance.